Harmonisasi Doktrin Tasawuf dan Al-Qur’an dalam Kitāb al-‘Ishq - Rohman, Saifir (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
The tendency to bring Sufism closer to the main sources of Shari'a in Indonesian contexts began in the 17th century. One manuscript that strongly indicates this phenomenon is the Kitāb al-'Ishq (The Nature of Jamāl and Jalāl), DS 0012 00001, a Sufism text from the Kuningan area which is thought to have been written in the 18th–19th centuries. This philological study aims to reveal how Kitāb al-'Ishq contributed to promoting philosophical Sufism, in this case the doctrine of Nūr Muḥammad, which in fact is part of the doctrine of Martabat Tujuh. This study shows that Kitāb al-'Ishq has at least two important contributions. First, Kitāb al-'Ishq contributes to showing the harmony of Nūr Muḥammad's doctrine with the Shari'a, namely by providing a number of Qur'ānī arguments. From a number of arguments presented, it appears that this text is still connected to the thoughts of several previous Middle Eastern Sufi figures, such as Saḥl al-Tustarī, al-Qushayrī and 'Abd al-Qādir al-Jīlānī. Second, Kitāb al-'Ishq shows the author's efforts to ground his doctrine, namely by using metaphors and analogies that are popular among Indonesian people in explaining the concept of Nūr Muḥammad with the aim of making it easy to digest and acceptable. Its position in Kuningan proves that in the Indonesian context, the tendency to harmonize Sufism with the Al-Qur'an and Hadith does not only occur in the Sumatra region, but also in West Java.